Multi-agent based simulation XVIII : International Workshop, MABS 2017, São Paulo, Brazil, May 8-12, 2017, Revised selected papers /: International Workshop, MABS 2017, São Paulo, Brazil, May 8-12, 2017, Revised selected papers. (2018) - Unknown
No abstract available